Engineered wetland for the treatment of wastewater from fertilizer plant - Sapari, N. (Trans Tech Publications Ltd, 2014)
This research analyzed the effective performance of a laboratory scale vertical surface flow constructed wetland (VSFCW) system, for the treatment of wastewater from fertilizer plant. Two reactors with a volume of 80 L each were used for the experiments. One of the reactors contains 2 units of floating plants known as water hyacinth (Eichhornia Crassipes) while the other was used as a control. The treatment was carried out in 2 phases: the wetland was first fed with treated domestic wastewater for acclimatization and stability and thereafter, fed continuously with analyzed wastewater samples from the fertilizer plant at the flow rate of 8 L/day, surface loading rate of 0.025 kg/m2/day for COD, 0.013 kg/m2/day for Ammonia, 0.021 kg/m2/day for Nitrate, 0.01 kg/m2/day for Nitrite, and 0.01 kg/m2/day for Phosphorus and a hydraulic detention time of 10 days. The treatment was monitored for 27 days and the performances evaluated. Results of the system indicated that the average removal efficiency was 47 for COD, 89.01 for ammonia, 83 for nitrate, 80 for nitrite, and 81 for phosphorus. The quality of the discharged effluent from the VSFCW showed that the system may be a viable technology for the wastewater treatment. Â© (2014) Trans Tech Publications, Switzerland.